Out of That Hole: Reflections of the Demetrian Myth in Six Contemporary Poems - Bijelić, Tatjana P. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
Focusing on the most revisited ancient mother-daughter myth, that of Demeter and Persephone, the paper engages with some of Demeter-centered appropriations of the myth in contemporary poetry written by women. Through continual reworkings of the archetypal story about the strongest primary bond between two biologically related females and their forced separation due to male intervention, women poets are increasingly addressing the qualities of Demeter’s new-era powers to regain her progeny and restore abundance. While concerned with possibilities of revival and regeneration, contemporary poetic renditions of the mythic framework offer a whole array of plots and images that tend to both perpetuate and challenge original versions of the myth by reassessing the dynamics of mother-daughter disengagement and reunion. The aim of the paper is to examine and juxtapose the strategies of performing the Demeter-Persephone myth in six contemporary Demetrian poems in which their authors extend the mythic space to incorporate other benevolent female characters and their journeys (Fainlight), situate their speakers and Persephones within a national tradition or a familiar setting (Boland), celebrate the birth of a new Persephone (Duffy), embrace the era of contradictions and its impacts on the female body (Ostriker), and fragmenting the myth through the use of various discourses to simulate instant yet profound interplays of deaths and revivals (O’Rourke).
Keywords: myth; Persephone; Demeter; contemporary poetry by women